Effects of postirradiation carboxymethylglucan administration in mice - Hofer, M; Pospísil, M; Viklická, S; Pipalová, I; Holá, J; Netíková, J; Sandula, J (International journal of immunopharmacology, 1995)
The hemopoiesis-enhancing ability of a soluble glucan derivative, i.e. carboxymethylglucan (CMG), was investigated in gamma-irradiated mice. Attention was focused on the usefulness of its single or repeated postirradiation administration. CMG was administered i.p. at (a) single dose of 6 mg 2 h postirradiation, (b) four 6 mg doses in the first 4 days postirradiation, (c) four 1.5 mg doses at the same time intervals. Indices of granulopoiesis and inflammatory side effects (liver weight increase and hepatic granulomas) were investigated in mice irradiated with a sublethal dose of 7 Gy. All three CMG-treated groups of mice were found to exhibit enhanced hemopoietic recovery in comparison with the controls. Although the mice repeatedly given the 6 mg CMG doses showed the most rapid recoveries of all the evaluated parameters of granulopoiesis, the most pronounced hepatic side effects were found in these mice, too. When survival of mice was recorded in lethally (9 Gy) irradiated animals, the best protective response were obtained following the repeated administration of the 1.5 mg CMG dose, the survival by day 30 in this group being significantly higher not only in comparison with the controls but also with the mice repeatedly given the 6 mg dose of CMG. The results suggest that the postirradiation CMG administration can be useful for enhancing radiation suppressed hemopoiesis. However, repeated larger CMG doses may produce side effects which compromise the overall survival of irradiated mice.
Keywords: játra; Bone Marrow; experimentální radiační poranění; Hematopoiesis; beta-glukany; beta-Glucans; zvířata; myši; Glucans; Mice; hematopoéza; Endotoxins; Stem Cells; Radiation Injuries, Experimental; Liver; Male; kostní dřeň; endotoxiny; glukany; kmenové buňky; Animals; mužské pohlaví